Synthesis, structure and crystallization behavior of amphiphilic hetero-arm molecular brushes with crystallizable poly(ethylene glycol) and n-alkyl side chains - Barnard, Elaine (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.